Party ID and election design: political parties in informal practices in Indonesian elections - George Towar Ikbal Tawakkal (Cogent Social Sciences)
Scholars studying party identification have largely overlooked informal practices such as money politics, often positioning voters with party identification solely as targets for money distribution. However, does party identification play only this role? This article aims to explore the presence of party identification within money politics, going beyond its function as a mere distribution target. Indonesia is chosen as the research site due to the evolution of its election design, frequent reports of money politics and the unique phenomenon of declining party identification alongside the repeated electoral victories of certain parties. Through in-depth interviews and observations conducted between 2022 and 2024 with over 100 intermediaries and voters, this study argues that party identification significantly influences the dynamics of money politics. Moreover, the shift in election design has led to a shift in the arena of party identification. While party identification may weaken in the context of voting behavior, it remains influential in money politics. The roles of Party ID intermediaries and Party ID money further support this argument.